The acceptability of different HIV testing approaches: cross-sectional study among GMSM in Australia - Yang, M.; Prestage, G.; Maycock, Bruce; Brown, Graham; de Wit, J.; McKechnie, M.; Guy, R.; Keen, P.; Fairley, C.; Zablotska, I. (BMJ Publishing Group, 2014)
Background: We explored the attitudes of Australian gay and other men who have sex with men (GMSM) about the current standard-of-care (non-rapid tests at healthcare settings) and alternative approaches (rapid tests and testing in non-healthcare settings) to better understand the acceptability of alternative testing approaches. Methods: The Contemporary Norms in Networks and Communities of GMSM study enrolled GMSM in Sydney, Melbourne and Perth in 2011–2012 using peer referrals. We explored the self-reported preferences for testing: rapid versus non-rapid and in non-healthcare settings (community-based or home-based testing) versus in healthcare settings, and examined factors associated with preferences for these approaches. Analyses of associations used standard univariate and age-adjusted logistic regression models. Results: Among 827 sexually active non-HIV-positive participants, 89% had been tested for HIV. Most preferred by participants was home rapid testing (46%), followed by standard-of-care (23%) and rapid testing in healthcare (20%) or community settings (7%). About 73% of participants preferred rapid over non-rapid testing, and 56% preferred testing in non-healthcare settings rather than in healthcare settings. Preference for rapid testing was associated with being fully employed (adjusted OR (aOR): 1.81; 95% CI 1.16 to 2.82), managerial/professional occupation (aOR: 2.03; 95% CI 1.19 to 3.46) and engaging in unprotected anal intercourse with casual partners (aOR: 1.89; 95% CI 1.29 to 2.78). The same factors were associated with preference for testing in non-healthcare settings. Conclusions: Australian GMSM prefer alternative testing approaches, possibly due to their convenience. The availability of new testing approaches may provide more options for GMSM at risk for HIV infection, improve access to HIV testing and potentially increase HIV testing rates.